The Effect of Work Discipline on Employee Performance which is Mediated with the Work Environment at the Education Department of the Hulu Sungai Utara District - Norhidayah; Singgih Priono; Misransyah Akos (East Asian Journal of Multidisciplinary Research, 2022)
The purpose of this study is to analyze and interpret the influence of Work Discipline mediated by the Work Environment on Employee Performance at the Education Office of Hulu Sungai Utara Regency. This research is quantitative research. The data sources are questionnaire and observation data. The sampling method in this study was determined by stratified proportional random sampling using a formula developed by Slovin. The data analysis technique used to test the hypothesis is path analysis, t test (t-test) and sobel test (sobel test). Based on the results of data analysis, it can be concluded that there is an insignificant effect of Work Discipline on Employee Performance at the Hulu Sungai Utara Regency Education Office, there is a significant influence of the Work Environment on Employee Performance. The results of the calculation of the sobel test work environment are able to mediate the effect of work discipline on performance at the Hulu Sungai Utara District Education Office.